2012
DOI: 10.1111/j.1440-1746.2011.06910.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil‐to‐lymphocyte ratio associated with mortality in early hepatocellular carcinoma patients after radiofrequency ablation

Abstract: High baseline NLR was associated with worse OS for patients with early HCC; post-RFA NLR predicted not only OS, but also tumor recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
105
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(114 citation statements)
references
References 35 publications
6
105
3
Order By: Relevance
“…Of these, NLR is one of the most simple and effective markers of inflammation and is linked with poor prognosis in various cancer types (26)(27)(28). Several studies demonstrated that an elevated NLR was associated with worse survival in patients with HCC who underwent radiofrequency ablation, TACE, resection and liver transplantation (29)(30)(31)(32). However, the exact association between a high NLR and poor prognosis has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, NLR is one of the most simple and effective markers of inflammation and is linked with poor prognosis in various cancer types (26)(27)(28). Several studies demonstrated that an elevated NLR was associated with worse survival in patients with HCC who underwent radiofrequency ablation, TACE, resection and liver transplantation (29)(30)(31)(32). However, the exact association between a high NLR and poor prognosis has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, increased NLR was demonstrated in cardiovascular and cerebrovascular diseases such as hypertension, unstable angina pectoris, myocardial infarction, transient ischemic attacks and stroke [9][10][11][12][13]. Moreover NLR has been found as a valuable index for predicting clinical outcomes in oncology [14][15][16][17] and inflammatory diseases such as Alzheimer, ulcerative colitis and appendicitis [18][19][20] . To our knowledge, this is the first study investigating the relationship between NLR levels and RAS.In this study we found that NLR levels in patients with RAS were higher than the control group.…”
Section: Discussionmentioning
confidence: 99%
“…PTA: pure tone average. cardiology (acute coronary syndromes, heart failure, and coronary revascularization procedures); end-stage renal disease; and inflammatory diseases such as Alzheimer, ulcerative colitis, and appendicitis [21,22]. A higher NLR indicates a higher level of inflammation [23].…”
Section: Discussionmentioning
confidence: 99%